INCREASING SELF-EFFICACY TO REGULATE EXERCISE IN ADULT PATIENTS WITH TYPE 2 DIABETES MELLITUS - Rinco Siregar; Sunantha Thongpat; Boontuan Wattanakul (Belitung Raya Foundation, 2018)
Background: Self-efficacy has been described as dominan factor associated with physical exercise in adult patients with type 2 diabetes mellitus, but to improve self-efficacy to regulate exercise of adult patients with type 2 diabetes mellitus is a challenge for health workers. Objective: This study was to determine the effect of exercise consultation program on self-efficacy to regulate exercise adults' patients of type 2 diabetes mellitus. Methods: A quasi-experimental study with two comparison groups was purposively designed for pre-test and post-test procedures. Sixty-one patients of type 2 diabetes mellitus were allocated into the experimental group (31 patients) and the control group (29 patients). While the experimental group received the exercise consultation for 12 weeks and routine care, the control group received routine care only. Comparative assessments on differences in self-efficacy to regulate exercise were examined both within and between groups using paired or unpaired t-test. Results: After receiving exercise consultation program, self-efficacy to regulate exercise significantly increased within the experimental group (p < .05), but there was no significant change with in the control group. Between groups, there was a significant difference self-efficacy to regulate exercise in adult patients with type 2 diabetes mellitus (p < .05). Conclusion: The exercise consultation program could increase self-efficacy to promote the physical exercise among adults patients of type 2 diabetes mellitus.